2016
DOI: 10.1007/s11695-016-2371-1
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Biliopancreatic Diversion with Duodenal Switch (BPD/DS) Over 9 Years

Abstract: Weight loss during the first year was well maintained, resolving comorbidities and improving quality of life. Rates of surgical complications resemble other bariatric procedures. Long-term nutrient deficiencies are of concern.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
17
1
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 63 publications
(28 citation statements)
references
References 30 publications
2
17
1
2
Order By: Relevance
“…The group of low responders (LWL) was composed of about 20% of patients. Similar results have been obtained in previous studies analyzing clinical outcomes of bariatric surgery (20,22), which makes biliopancreatic diversion with duodenal switch a very successful weight loss therapeutic option with regard to the extent of weight loss and long-term weight loss maintenance (23). The relatively moderate impact of polygenic risk scores on weight loss in the present study could be due to the fact that biliopancreatic diversion with duodenal switch is a very effective surgery, which probably explains why the benefit of adding a polygenic risk score to prediction models, though significant, is not as strong as expected.…”
Section: Discussionsupporting
confidence: 89%
“…The group of low responders (LWL) was composed of about 20% of patients. Similar results have been obtained in previous studies analyzing clinical outcomes of bariatric surgery (20,22), which makes biliopancreatic diversion with duodenal switch a very successful weight loss therapeutic option with regard to the extent of weight loss and long-term weight loss maintenance (23). The relatively moderate impact of polygenic risk scores on weight loss in the present study could be due to the fact that biliopancreatic diversion with duodenal switch is a very effective surgery, which probably explains why the benefit of adding a polygenic risk score to prediction models, though significant, is not as strong as expected.…”
Section: Discussionsupporting
confidence: 89%
“…The observed weight loss after RYGB and BPD/DS in this study was not surprising since several previous studies comparing the two methods in patients with super obesity have found similar results [ 10 , 17 , 18 ], and it has previously been pointed out that weight loss is more sustained after BPD/DS [ 19 ]. In a recent American study by Strain et al [ 20 ], a sustained BMI reduction from 53.4 to 31.5 kg/m 2 was observed throughout the 9 years of observation after BPD/DS. Two previous studies [ 8 , 9 ] observed that more than 50% of the super obese patients still had a BMI >35 kg/m 2 after RYGB.…”
Section: Discussionmentioning
confidence: 94%
“…The four most commonly performed bariatric procedures today are sleeve gastrectomy, RYGB, and laparoscopic adjustable banding. [43][44][45][46][47][48][49][50][51][52][53] Laparoscopic sleeve gastrectomy (LSG) is considered primarily a restrictive operation in which 80% of the stomach is removed, resulting in a remaining smaller tubular stomach that holds significantly less volume. 44 In addition to reducing stomach volume, LSG reduces ghrelin production and enhances peptide YY levels, which can significantly affect appetite and increase the procedure's weight loss efficacy.…”
Section: Surgical Weight Loss Therapiesmentioning
confidence: 99%